Social media and the role of libraries during the COVID-19 pandemic - Dessy Harisanty; Rahma Sugihartati; Koko Srimulyo (Masyarakat, Kebudayaan dan Politik, 2022)
The COVID-19 pandemic has had a huge impact on a person’s life, both physically and mentally. With the amount of information available, people can use this information to overcome the anxiety they face. This study aims to identify the information behavior of COVID-19 survivors and the role of libraries in social media as information institutions during the COVID-19 pandemic. The research method used is quantitative descriptive. Data collection was carried out through a survey using Google Forms. The number of data collected was 148 respondents. The location was East Java, including Surabaya, Sidoarjo, Tuban, Bangkalan, Magetan, Blitar, Situbondo, Jombang, Gresik, Kediri, Ponorogo, Lamongan, Madiun, Ngawi, Banyuwangi, and Tulungagung. The results show that most people fulfill their information needs regarding the treatment of COVID and its development (48.6%), as well as a healthy lifestyle (15.5%) through social media. In accessing information, a small number of respondents experienced obstacles such as the amount of hoax information (6.1%), the available information was considered incomplete (5.4%), limited internet quota (4.1%), and problematic network signal (4.1%). Based on these results, we need the role of libraries that are able to provide information to meet the information needs of users.